Новые роды цикадовых семейства Delphacidae (Homoptera Auchenorrhyncha) из Казахстана - Емельянов, А.Ф. (Вестник зоологии, 1972)
Two new genera — Dicentropyx, gen. n. (the type species Eurysa sublineata E m.)
and Issedonia, gen. n.) the type species Calligypona cochlearia Em.) and two new combinations— Kusnezoviella venustula (Em.), comb. n. —Calligypona venustula Em. and Falcotoya minuscula (Н о г v.), comb. n. =Delphax minuscula Horv . are described in
the article.